2016
DOI: 10.1038/ncomms11834
|View full text |Cite
|
Sign up to set email alerts
|

Lasting mantle scars lead to perennial plate tectonics

Abstract: Mid-ocean ridges, transform faults, subduction and continental collisions form the conventional theory of plate tectonics to explain non-rigid behaviour at plate boundaries. However, the theory does not explain directly the processes involved in intraplate deformation and seismicity. Recently, damage structures in the lithosphere have been linked to the origin of plate tectonics. Despite seismological imaging suggesting that inherited mantle lithosphere heterogeneities are ubiquitous, their plate tectonic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 52 publications
8
68
0
Order By: Relevance
“…Our interpreted crustal architecture aligns with the mantle architecture interpreted by Skirrow et al () (Figure ), where both IOCG and CGG deposits lie along major structural breaks that connect different compartments of the mantle to the crust along long‐lasting lithospheric scars (in the sense of Heron et al, ). The oldest crustal fragment represented by Domain C is mostly rooted by the metasomatized lithospheric mantle.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our interpreted crustal architecture aligns with the mantle architecture interpreted by Skirrow et al () (Figure ), where both IOCG and CGG deposits lie along major structural breaks that connect different compartments of the mantle to the crust along long‐lasting lithospheric scars (in the sense of Heron et al, ). The oldest crustal fragment represented by Domain C is mostly rooted by the metasomatized lithospheric mantle.…”
Section: Discussionsupporting
confidence: 88%
“…Most large mineral systems require the existence of geological structures (e.g., sets of faults, shear zones, and folds) that provide physical pathways for crucial large‐scale fluid plumbing through the lithosphere to the crust (Huston et al, ). However, the identification of these structures is difficult because rocks are often reworked, structures are reactivated, and deformation superimposed over time or is buried by younger rocks (Heron et al, ). Furthermore, the task of distinguishing between shallow and deep penetrating structures is challenging due to data resolution, the ambiguity of geophysical techniques, and the physical properties of geological materials (Huston et al, ; Korsch & Doublier, ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that it is indeed unexpected that applying a North Atlantic Craton mantle suture (Figure b) in the presence of an extension field that is relevant in velocity and orientation to the Paleogene (Figure ) would produce appropriate rift dynamics for the Davis Strait system (Figure ). However, the study here complements a growing body of work that highlights the potential of the mantle lithosphere to play an important role in tectonic processes (Pysklywec & Beaumont, ; Babuška & Plomerová, ; Heron et al, ; Jourdon et al, ; Salazar‐Mora et al, ; Phillips et al, ; Balázs et al, ; Heron et al, ).…”
Section: Discussionsupporting
confidence: 61%
“…Numerous previous studies have shown the potential for mantle lithosphere structures to control the evolution of shallow tectonics (Balázs et al, ; Heron et al, ; Heron et al, ; Jourdon et al, ; Pysklywec & Beaumont, ; Phillips et al, ; Salazar‐Mora et al, ; Schiffer et al, ), highlighting a deep genesis for lithosphere‐scale deformation (e.g., Holdsworth et al, ; Vauchez et al, ). Reactivation of features formed through previous collisional or rifting events (Wilson, ) is well established and thought to occur along well‐defined, preexisting structures such as faults, shear zones, or lithological contacts (Holdsworth et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Deep seismic reflection surveys have long suggested relics of subduction zones in the mantle lithosphere (Morgan et al, 1994), and their link to suture zones has been well-pointed by the compilations of Heron et al (2016). For instance, in the rifted conjugate margins between Norway and Greenland in the North Sea (North Atlantic), relicts of subduction zones were seismically interpreted and associated to the Caledonian orogenic belt (Schiffer et al, 2014), which is the suture through which the following North Sea rifting took place.…”
Section: Discussionmentioning
confidence: 99%